Analisis Kemampuan Pemecahan Masalah Matematis pada Siswa Kelas IV SD dalam Menyelesaikan Soal Pecahan - Aodra Fahru Riza; Isqina Lulu’ul Afifah; Nuzulun Niswah; Diana Ermawati (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the mathematical problem solving ability of fourth grade elementary school students in solving fraction problems at SD 2 Temulus. This type of research is descriptive qualitative research. The data source of this research comes from the answers to the daily test results of fraction material and interviews. This study used 3 subjects from 12 fourth grade students who were taken using purposive techniques according to the category of mathematical problem solving ability, consisting of high, medium, and low categories. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman model which includes four stages of data reduction, data presentation, conclusion drawing. The results showed that (1) students with high ability were able to fulfill all Polya problem solving indicators. (2) students in the medium category can solve problems well, but often lack thoroughness and are often hasty. They can only fulfill 2 of the 4 problem solving indicators. (3) Students in the low category have not been able to solve the problem well. They were unable to fulfill all indicators of problem solving ability according to Polya's stages. The conclusion of this study is that students have various potentials in mathematical problem solving ranging from high, medium, and low categories.